2014
DOI: 10.5194/bg-11-1371-2014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring interacting influences on the silicon isotopic composition of the surface ocean: a case study from the Kerguelen Plateau

Abstract: Abstract. This study presents six new water column profiles of the silicon isotopic composition (δ 30 Si) of dissolved silicon (DSi) from the Atlantic and Indian sectors of the Southern Ocean and a variable depth box model of silica cycling in the mixed layer that was constructed to illuminate the evolution of surface ocean δ 30 Si over the full course of a year. In keeping with previous observations, δ 30 Si values ranged from +1.9 to +2.4 ‰ in the mixed layer (ML), +1.2 to +1.7 ‰ in Winter Water (WW), and +… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Previous studies have suggested that the effects of fractionation during dissolution should be considered when interpreting paleoceanographic reconstructions based on δ 30 Si (e.g., Coffineau et al, 2014). This simple model, combined with the sediment trap time series, gives the opportunity to test the effect of silicon isotope fractionation during dissolution of BSi in the water column.…”
Section: Paleoapplications Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the effects of fractionation during dissolution should be considered when interpreting paleoceanographic reconstructions based on δ 30 Si (e.g., Coffineau et al, 2014). This simple model, combined with the sediment trap time series, gives the opportunity to test the effect of silicon isotope fractionation during dissolution of BSi in the water column.…”
Section: Paleoapplications Of the Modelmentioning
confidence: 99%
“…To date, only three papers have attempted to describe the seasonal Si biogeochemical and isotopic cycle in the Southern Ocean using modelling approaches (Coffineau et al, 2014;De Brauwere et al, 2012;Fripiat et al, 2012). None of them consider the history of particles during their descent through the water column nor do they integrate the seasonality of parameters that control the recycling of BSi at depth.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate layers of the section were represented by LSW, Mediterranean Water (MW), Subarctic Intermediate Water (SAIW), and Polar Intermediate Water (PIW). LSW is the last stage of the transformation of SPMWs and forms in the Labrador and Irminger seas (e.g., Pickart et al, 2003;de Jong and de Steur, 2016;Fröb et al, 2016). MW enters the North Atlantic from the Mediterranean Sea through the Strait of Gibraltar (Ambar and Howe, 1979;Baringer and Price, 1997).…”
Section: Optimum Multiparameter Analysis Tomentioning
confidence: 99%
“…4c) extending to depths below 2000 m, reflecting the presence of LSW. This water mass, which contributes to NADW, is formed by deep convection in the Labrador and Irminger seas (e.g., de Jong and de Steur, 2016) and spreads across the North Atlantic at intermediate to middle depths (see Fig. 1).…”
Section: Relationship Between North Atlantic δ 30 Si Dsi Distributionmentioning
confidence: 99%
See 1 more Smart Citation